Hubungan Perilaku Merokok Dengan Derajat Keparahan Aterosklerosis pada Pasien Penyakit Jantung Koroner : The Correlation of Behavior of Smoking by Degrees Severity of Atherosclerosis in Patients of Coronary Heart Disease - Karmitasari Yanra Katimenta; Kristin Rosela; Taupik Rahman (Jurnal Surya Medika (JSM), 2023)
Atherosclerosis that occurs in the heart arteries is called coronary heart disease, which is narrowing and hardening of the coronary arteries in the heart. Atherosclerosis is influenced by several factors, one of which is smoking behavior, as one of the risk factors that can worsen atherosclerosis. However, there are no studies that link smoking behavior to the severity of atherosclerosis in the invasive diagnostic space and intervention of the heart and blood vessels of the RSUD dr. Doris Sylvanus Palangka Raya. The study was to determine the relationship of smoking behavior with the severity of atherosclerosis in patients with coronary heart disease in the invasive diagnostic room and intervention of the heart and blood vessels of RSUD dr. Doris Sylvanus Palangka Raya. This study was conducted using a cross-sectional method, using accidental sampling sampling techniques through questionnaires and coronary angiography observation sheets with 30 respondents who were coronary heart patients who underwent coronary angiographic examination in the Invasive Diagnostic Room and Intervention of the Heart and Blood Vessels of RSUD from . Doris Sylvanus Palangka Raya. From this study ρ (P Value) is 0.004, which means there is a relationship between smoking behavior and the severity of atherosclerosis in coronary heart disease patients in the Invasive Diagnostic Room and Intervention of the Heart and Blood Vessels of RSUD dr. Doris Sylvanus Palangka Raya. There needs to be information about the dangers of smoking behavior that nurses can give to patients, and further research is carried out on the factors that influence the severity of other atherosclerosis both those that can be modified and those that cannot be modified.